Should the City of Cape Town plan for fully autonomous vehicles? - Attwood, Craig (Department of Civil Engineering, 2022)
Background The City of Cape Town's Comprehensive Integrated Transport Plan (CITP) 2018 to 2023 identifies public transport as the key driver to changing the spatial form of Cape Town, with all its urban inefficiencies and social inequality. A key element to building sustainable communities is the establishment of Transit Oriented Developments (TODs) at the right locations along the rail and BRT transport corridors. However, the Metrorail railway service in Cape Town, which should be the backbone of the public transport system, has collapsed because of issues with safety, reliability, vandalism and comfort. This has forced commuters to opt for other modes of transport, mainly private vehicles and minibus taxis (MBTs), which has contributed to Cape Town becoming the most congested city in South Africa. Autonomous vehicles have been touted as the elixir for the problems of road safety and congestion. Along with their ability to find the most efficient routes they are anticipated, inter alia, to be able to free up road space by decreasing the following distance between vehicles Aim The aim of this dissertation is to describe an autonomous vehicle, review the current status of the industry in the evolution towards driverless cars, and predict how autonomous vehicles will be able to penetrate and impact the road transport network of South Africa, with a particular emphasis on Cape Town and the MBT industry. Method The research method included a literature study of the research and development happening in the Global North and how this would benefit South Africa, along with a Delphi Survey of a panel of experts in the field of South African road transport. Findings The literature review and Delphi survey produced the following propositions: • The high-stakes competition between car manufacturers and technology companies to produce the first driverless car that will be legally allowed to drive on all roads, will ensure that this will happen – however the timeline is not so clear. • When it does happen, the condition of the road reserve will be one of the factors in preventing driverless cars from operating freely. The quality of the road infrastructure, only 20% South Africa's roads are paved, and the unpredictability of other road users such as pedestrians, cyclists and, in South Africa, livestock, will mean that there will probably always have to be someone behind the wheel of an autonomous vehicle even if it is legally self-driving. • The MBT industry in South Africa does not receive an operating subsidy from the Government but it is an extremely powerful and influential informal public transport provider, often at odds with the lawmakers and the traffic authorities. It is important that the Government and the MBT industry aim to form a working partnership so that the road transport industry can take advantage of the obvious benefits of this new technology. • Because the Government is ensuring that public transport is given priority over private transport, it is unlikely that it will consider the huge investment in the road infrastructure that is needed to support self-driving vehicles. But, if the Government and the MBT industry could find a way for the MBT industry to become a formal part of the public transport system, it may then consider portioning some of its public transport budget for road infrastructure upgrades to support autonomous MBTs. • The evolutionary road to fully autonomous vehicles (Level 5) is long. There are already cars on the road in the Global North that have autonomy Level 2, and some between Level 2 and 3 (Level 2+), with technology that allows the cars to change lanes, keep a safe distance from surrounding cars, etc.. As communication is from vehicle to vehicle, Level 2 and 2+ vehicles do not require the huge capital outlay for the infrastructure and communications network that would be necessary for Level 3, 4 and 5 vehicles. No MBT in South Africa has any form of autonomy, and, with 3 out of the 36 people killed daily on the road involved in accidents with MBTs, it is imperative that the Government finds a way for the industry to benefit from the safety aspects of autonomy Levels 2 and 2+. • One of the major threats of the 4th Industrial Revolution is job losses. Historically, MBT, e-hailing and metered taxi drivers have been known to violently defend their livelihoods when faced by competition for their passengers. The arrival of driverless vehicles will certainly be a threat to their jobs, and it is likely that the drivers will resort to any means possible to prevent this from happening. However, prevailing conditions, such as the poor condition of the road reserve and the lack of government resources and financial input, means that these changes are not imminent, and, in the meantime, structures can be put in place to soften the impact that autonomy will have on job losses in the taxi industry. Conclusions Should the City of Cape Town plan for fully AVs? Yes. Features found in Levels 1 and 2 should become mandatory in all vehicles on the road. Planning can be done in phases, initially to support vehicles at Levels 1, 2 and 2+, by improving the road infrastructure such as lane markings and defining kerbsides, and then, more improvements for Level 3 and the finally for Levels 4 and 5 installing the telecommunications network and upgrading the whole road reserve. Cyclists and pedestrians are a major hinderance in the evolution of AVs, their unpredictable behaviour is very difficult for the vehicle's software to process. NMT is an important part of the future of Cape Town's transport system and the upgrades and extensions to pathways should be carried out with the intention of limiting the interaction with AVs. There are some benefits for South Africa being behind in the adoption of AVs in that they can learn from mistakes made by the many international cities that are presently going through the roll out of AVs. In the meantime, priority should be given by the City, to working alongside the Government, to restoring and improving the rail service to a level that will attract commuters back to this mode of transport to reduce the unsustainable pressure on the roads. Although the evolution to driverless cars is unpredictable, it is important that all levels of government engage with as many stakeholders and affected parties as possible before putting legislation in place. This is an important time in the history of road transport and every effort needs to be made to get the maximum benefit out of all the positive impacts that this technology will bring.